Modelos matemáticos para o problema integrado de dimensionamento de lotes e corte de estoque unidimensional - Longhi, Aneliza Leandro [UNESP] (2015)
The lot-sizing and the one-dimensional cutting-stock problems play an important role in several production sectors, such as, tubular furniture factories, paper plants, and metallurgical industries. These problems are generally dealt independently. In this work, we approached both problems in an integrated way. We considered a classical model for lot sizing problem and its reformulation based on the shortest path problem. Concerning the one-dimensional cutting stock problem, we extend three different models from literature considering multiple periods. Based on the models studied, we proposed formulations that treat the problems in an integrated way. A computational study was performed using randomly generated data. The aim of this study was to assess the quality of integrated models in different aspects.